2016
DOI: 10.1002/pip.2854
|View full text |Cite
|
Sign up to set email alerts
|

23.2% laser processed back contact solar cell: fabrication, characterization and modeling

Abstract: We describe the manufacturing process for interdigitated back contact back junction silicon solar cells based on laser processes, and present detailed results and analysis to our best cell efficiency of 23.24%. The manufacturing process features two laser doping steps, one for the boron doped emitter and one for the phosphorus doped back surface field. The saturation current densities of thermal oxide passivated laser doped regions are on par with furnace diffused silicon for high efficiency solar cells. Laser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 33 publications
1
18
0
2
Order By: Relevance
“…Laser processing has been widely studied for silicon device fabrication, including laser ablation, micro-texturing, doping, transfer of metal contacts, and annealing (Dahlinger et al 2017). The major challenge, however, is presented by laser-induced structural disorder and defects, which can dramatically degrade the electrical properties of laser-processed silicon and negatively affect the performance of laser-based photovoltaic (Hameiri et al 2010) and microelectronic (Arora and Dawar 1996) devices.…”
Section: Introductionmentioning
confidence: 99%
“…Laser processing has been widely studied for silicon device fabrication, including laser ablation, micro-texturing, doping, transfer of metal contacts, and annealing (Dahlinger et al 2017). The major challenge, however, is presented by laser-induced structural disorder and defects, which can dramatically degrade the electrical properties of laser-processed silicon and negatively affect the performance of laser-based photovoltaic (Hameiri et al 2010) and microelectronic (Arora and Dawar 1996) devices.…”
Section: Introductionmentioning
confidence: 99%
“…Diğer taraftan, Tablo 1'de verilen güneş hücrelerinin verimlerinin, literatürdeki bir kısım güneş hücrelerinin verimlerine kıyasla, nispeten düşük olduğu görülmektedir [2][3][4][5][6][7][8]. Düşük verim, iki yarı iletken arasındaki tükenme bölgesindeki yüklerin yeniden birleşmesinden dolayı ya da gazların geçmesine izin verecek şekilde gözenekli bir yapıya sahip olan ZnO filminin yapısı nedeniyle olabilmektedir [26].…”
Section: Introductionunclassified
“…Dahlinger et al performed large‐area laser doping to minimize the required patterning steps and recently demonstrated a device efficiency of 23.2% with this process utilizing two‐different laser systems for four laser steps. Franklin et al demonstrated an all‐laser‐doped IBC cell concept using localized laser doping with a device efficiency of 19.1% while a cell with photolithographic patterning steps achieve 24.4% …”
Section: Introductionmentioning
confidence: 99%
“…However, we highlight, that these laboratory processes can be substituted with for instance laser‐patterning for contact separation (such as in Ref. ) or other low‐cost passivation techniques.…”
Section: Introductionmentioning
confidence: 99%